KANDUNGAN KIMIA BERBAGAI EKSTRAK DAUN MIANA (COLEUS BLUMEI BENTH) DAN EFEK ANTHELMINTIKNYA TERHADAP CACING PITA PADA AYAM - Yusuf Ridwan; Latifah K Darusman; Fadjar Satrija; Ekowati Handaryani (Jurnal Ilmu Pertanian Indonesia, 2006)
Study on the chemical compound of painted nettle (Coleus blumei Benth) leave extract and its anthelmintic activity against chicken tapeworm were conducted. Leave of painted nettle were collected and extracted with hexane, chloroform, ethanol and water. Phytochemical analysis was carried out to determine the chemical compound of secondary metabolites. Anthelmintic activity was evaluated with an assay using chicken tapeworm in a serial microplate dilution method by determination of efective concentration 50 (EC50) using probit analysis. The result of phytochemistry analysis showed that Coleus leaves consisted of flavonoid, steroid, tannin and saponin. Three of four extracts displayed strong anthelmintic activity with the higest activity belong to chloroform extract with EC50 5 mg/ml followed by n-hexane 9 mg/ml and metanol extract 10,2 mg/ml, while water extract has a weak anthelmintic activity with 106,2 mg/ml. In general, chloroform extract proved to be a more efficient extractant of biologically active compounds than either hexane, ethanol or water extract. The promising activity displayed by a number of extracts has led to further investigation of the active compound. Unfortunately, the result of invivo assay showed that the chloroform extract treatment with dose level 25 mg/kg BW could not to reduce the number of tapeworm in chicken. It is interesting for further investigate the differences of respon between in vitro and in vivo to determine involved factors.